Causes and consequences of DNA content variation in Zea - González, Graciela Esther (2022)
Cytogenetic evidence indicates that Zea, which comprises maize (Z. mays ssp. mays) and its wild relatives, is an allopolyploid genus. Our research group has carried out numerous cytogenetic studies on Zea species, mainly focused on native Argentinian and Bolivian maize landraces. We found a wide inter- and intraspecific genome size variation in the genus, with mean 2C-values ranging between 4.20 and 11.36 pg. For the maize landraces studied here, it varied between 4.20 and 6.75 pg. The objectives of this work are to analyze the causes of genome size variation and to discuss their adaptive value in Zea. This variation is mainly attributed to differences in the heterochromatin located in the knobs and to the amount of interspersed DNA from retrotransposons. Polymorphisms in presence or absence of B-chromosomes (Bs) and the population frequency of Bs are also a source of genome size variation, with doses ranging between one and eight in the landraces analyzed here. Correlation analysis revealed that the percentage of heterochromatin is positively correlated with genome size. In addition, populations cultivated at higher altitudes, which are known to be precocious, have smaller genome sizes than do those growing at lower altitudes. This information, together with the positive correlation observed between the length of the vegetative cycle and the percentage of heterochromatin, led us to propose that it has an adaptive role. On the other hand, the negative relationship found between Bs and heterochromatic knobs allowed us to propose the existence of an intragenomic conflict between these elements. We hypothesize that an optimal nucleotype may have resulted from such intranuclear conflict, where genome adjustments led to a suitable length of the vegetative cycle for maize landraces growing across altitudinal clines.